Synthesis, Crystal Structure, and Luminescent Properties of a New Holmium(III) Coordination Polymer Involving 2,5-Dihydroxy-1,4-terephthalic Acid Dianion as Ligand - Jiaqi Li (MDPI AG, 2021)
A novel coordination polymer {[Ho2(DHTA)3(H2O)5]·H2O}n (1) was synthesized by hydrothermal synthesis (DHTA = 2,5-dihydroxy-1,4-terephthalic acid anion). The crystallographic data show that complex 1 crystallizes in a triclinic system with space group P<mover>1¯</mover>, with a = 9.6617(17) Å, b = 11.902(2) Å, c = 13.284(2) Å, α = 100.617(3)°, β = 92.765(2)°, γ = 106.715(2)°, V = 1429.6(4) Å3, Z = 2, C24H24O24Ho2, and Mr = 1026.290. Complex 1 contains two eight-coordinated metal centers Ho(III). The TGA results show that the weight loss can be ascribed to the removal of the organic component from 400 to 650 °C. At the temperature above 650 °C, the residue is Holmium(III) oxide (Ho2O3). The luminescent results reveal that the complex has potential application as a new green luminescence material.